Handbook of child custody - Goldstein, Mark L., 1948- (Springer, 2016)
This authoritative reference brings together leading experts for up-to-date theory, findings, and guidelines on the core aspects of child custody evaluations. Contributors offer steps for gathering more accurate family data through home observations, interviews, and collateral information. Chapters examine psychological assessment tools commonly used in evaluations, including measures relating to parenting competencies, mental illness, domestic violence, and substance abuse, and consider increasingly salient issues such as relocation and families in therapy. The section on case studies shows best practices applied in real-life custody situations, and a chapter authored by a family court judge offers rarely-seen perspective from the bench. Featured in the Handbook: a survey of ethical and professional issues; observing and interviewing children, adolescents, and adults; psychological assessment and personality testing; a detailed review of the Bricklin scales; specialized issues, including parental alienation, attachment, cults, and more; illustrative case studies and psychological reports. Mental health professionals who conduct child custody evaluations, including psychiatrists, clinical psychologists clinical social workers, family and marriage counselors, and licensed clinical professional counselors, will appreciate the Handbook of Child Custody. Family law attorneys will also find the Handbook useful in assisting them in child custody litigation. Its thorough coverage will aid evaluators in making recommendations that are professional, ethical, and impartial, and family lawyers in understanding the evaluation process and preparing for expert testimony.